2013
DOI: 10.1590/0104-1169.3224.2369
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction among health care workers: the role of gender and age

Abstract: OBJECTIVE: to analyze the influence of gender and age on the quality of the professional lives of health care professionals at a university hospital. METHOD: a total of 546 professionals completed a general questionnaire that measured sociodemographic variables and evaluated job satisfaction using a scale adopted from the NTP 394 Job Satisfaction scale and translated into Spanish. RESULTS: overall, 77.2% of the professionals surveyed were satisfied with the work they perform. With regards to gender, we found o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
36
7
19

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 11 publications
10
36
7
19
Order By: Relevance
“…On the other hand, in a study carried out by Adams in 2000, it is found that at older age there is a greater dissatisfaction due to the monotony of work [10], and in the present investigation it was found that the young population reported being more dissatisfied in most categories, unlike older service providers. In this study, the male population was most satisfied, in contrast to was found in a study carried out by Carrillo and co-workers in 2013, which indicates that women show greater satisfaction than men with work or activity they perform [11].…”
Section: Discussioncontrasting
confidence: 96%
“…On the other hand, in a study carried out by Adams in 2000, it is found that at older age there is a greater dissatisfaction due to the monotony of work [10], and in the present investigation it was found that the young population reported being more dissatisfied in most categories, unlike older service providers. In this study, the male population was most satisfied, in contrast to was found in a study carried out by Carrillo and co-workers in 2013, which indicates that women show greater satisfaction than men with work or activity they perform [11].…”
Section: Discussioncontrasting
confidence: 96%
“…[18] However, some studies on health-care workers have identified a significant relationship between WRQoL and gender. [414]…”
Section: Discussionmentioning
confidence: 99%
“…[34] In comparison to other quality of work life scales, the WRQoL scale is unique as it measures various factors related to work as well as nonwork factors like general well-being (GWB) in addition to the “homework interface” (HWI). [45] This study attempts to validate the bilingual (English and Marathi) WRQoL scale and assess the WRQoL perceived by employees of a corporate hospital in Pune City.…”
Section: Introductionmentioning
confidence: 99%
“…De ahí que diseñaron una escala bidimensional para medir la sa sfacción laboral, sin embargo, aunque ha sido muy u lizada en contextos laborales, en diferentes grupos profesionales y en varios países (Flores, 2001;Raineri, 2007;Alonso, 2008;Tejedo, 2013;Alonso, Pozo, Hernán-dez, Díaz, Mar nez, & Valera, 2005;Fernández, 2008;Herrera-Amaya, & Manrique-Abril, 2008;Bobbio, & Ramos, 2010;Carrillo-García, Solano-Ruíz, Mar nez-Roche, & Gómez-García, 2013;Escobedo, Cuautle, Maynez, & Estebané, 2014;Depolo, & Bruni, 2015;Goetz, Marx, Marx, Brodowski, Nafula, Prytherch, Omogi Awour, & Szecsenyi, 2015); recientes estudios psicométricos, hechos en el Perú, no han podido verificar su estructura bifactorial (Boluarte, 2014;Boluarte, & Merino, 2015).En ese sen do, la sa sfacción laboral en el Perú, es un tema que ha sido tocado por los estudios empíricos de Federico León, quien realizó un análi-sis de los constructos y supuestos teóricos de la teoría bifactorial de Herzberg (León, & Sepúlveda, 1979) y de la teoría instrumental de Vroom (León, 1981). Aunque en un primer momento, los estudios sobre sa sfacción laboral, se llevaron a cabo, principalmente, en la ciudad de Lima; en los úl mos años, nuevos estudios se han realizado en la ciudad de Arequipa.…”
unclassified